Etiological and pathological studies on bacterial abortions of sheeps and cattles in north-east anatolia region - Yavuz S. Sağlam; S. Serap Türkütanıt; Rüştü Taştan; Hidayet Bozoğlu; Salih Otlu (Eurasian Journal of Veterinary Sciences)
In this study were examined bacteriological etiology and pathologically findings of 96 cattle 119 sheep aborted fetuses in North-East Anatolia Region examined beetwen 1994-1996. In Erzurum Province, 42.25 % Brucella spp., 1.40 % Haemophilus somnus, 1.40 % Corynebacterium spp., 1.40 % Salmonella dublin in bovine aborted fetuses and 45.23 % Brucella spp., 2.38 % Corynebacterium spp., 5.95 % Salmonella abortus ovis, 3.57 % Campylobacter fetus subspp. in sheep aborted fetus were isolated. In Kars Province , 40 % Brucella spp., 1.04 % Campylobacter fetus in bovine aborted fetuses and 5.70 % Campylobacter fetus, 5.71 % Salmonella spp., 1.19 % Streptococcus spp. in sheep aborted fetuses were isolated. Etiology of the bacteria could not be determined on the average 54.81 % aborted fetuses. Histopathologically, catarrhal bronchopneumonie, nonpurulent interstitial nephritis, diffuse or focal necrosis in the liver, degeneration in hepatocytes were observated. Congenital malformations including scoliose, arthrose, prognathie, cerebellar hypoplasie and ichtyosis congenita and were delected in 3 catlles and 4 sheeps fetuses.